p(x)=(x-1) (x+1) solve this
Answers
Answered by
1
Answer:
X= 1 or -1 as when we put X =1 then
X= 1 or -1 as when we put X =1 then p(1)= (1-1)(1+1)=0×2=0
X= 1 or -1 as when we put X =1 then p(1)= (1-1)(1+1)=0×2=0and when we put X=-1 then
X= 1 or -1 as when we put X =1 then p(1)= (1-1)(1+1)=0×2=0and when we put X=-1 then p(-1)=(-1-1)(-1+1)=-2×0= 0
Answered by
8
Answer:
USE THE identity a^2-b^2 =(a+b)(a-b_)
u will get ur answer
Step-by-step explanation:
HOPE U CAN D0 IT
Similar questions
Social Sciences,
6 months ago
Computer Science,
6 months ago
Math,
6 months ago
Environmental Sciences,
1 year ago
English,
1 year ago
Chemistry,
1 year ago